Frequency of Wound Infection after Duodenal Ulcer Perforation Repair - Sonia Rahim Khan, Jamshed Alam, Muhammad Marwan, Shahinda, Laila Khan, Naseem-Ur-Rahman, Romana Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of wound infection after duodenal ulcer perforation repair. Methodology: This descriptive Case series Study in the department of Surgery, Khyber Teaching Hospital from February 2021-July 2021, Peshawar. A total of 123 patients with perforated duodenal ulcer, included those aged 20 to 60 years. Immuno-compromised patients, CRF & CLD were excluded. A single dose of broad-spectrum antibiotic was given prior to undergone open repair by a consultant surgeon followed by two more shorts of antibiotic given post operatively at the interval of 8 hours each. Patients were followed postoperatively for 4 weeks and surgical site infection was noted. Results: The study patients age ranged from 20 to 60 years, with a mean age of 43.77±9.35 years. Most of the patients 77(62.60%) were in the 20–40 years age range.Male to female ratio of these 123 cases was 2.1:1, with 83(67.48%) males and 40(32.52%) females. In our study, frequency of wound infection after duodenal ulcer perforation repair was found in 28(22.76%) patients. Conclusion: This study concluded that the clinicians should take some practical recommendations regarding control of surgical site infectionsin order to lower the morbidity and mortality of these specific patients. Keywords: perforated duodenal ulcer, open repair,surgical site infection.